Health system financing paradigm in the state of São Paulo: a regional analysis - Soares, Adilson (Revista de Saúde Pública, 2019)
OBJECTIVE: To analyze the allocation of financial resources in the Brazilian Unified Health System (SUS) in the state of São Paulo by level of care, health region, source of funds and level of government. METHODS: This is an exploratory study based on 2014 data extracted from the Public Health Budget Database, presented in absolute terms, relative terms and per capita. RESULTS: In 2014, R52.1 bi were spent on public health, 58.0% having corresponded to the expenditures of the municipalities and 42.0% to those of the state government. Regional per capita spending varied from R561.75 to R824.85. As for the per capita spending on primary health care, which represented 37.5% of the municipalities’ total expenditure, the lowest value was found in the city of São Paulo and the highest, in Araçatuba. Campinas had the highest per capita expenditure on medium and high complexity care, while Presidente Prudente had the lowest. The highest regional percentage of the current net revenue spent on health was verified in Registro, and the lowest, in the city of São Paulo. CONCLUSIONS: The paradigm of the health sector’s financing in São Paulo revealed that the expenditure on primary health care, level elected by health policy as strategic because it depends on coordination and integral health care in the attention networks, was not considered a priority in relation to the expenditure with the medium and high complexity, exposing the iniquities in the state’s regions.